Chiado Of Once, Chiado Of Nowadays: Fashion Diffusion, Urbanization and Revitalization of Historic Areas (ModaPalavra e-periódico, 2017)
On the context of a doctoral thesis’ development, as we studied Fashion and its historical development in Portugal during the 19th and 20th centuries, we identified  Chiado - a district located in Lisbon - as an extremely important focus point for the dissemination of Fashion in Portugal . In the past, Chiado was frequented by the wealthiest classes of Lisbon – namely the nobility, the aristocracy, the bourgeois, as well as by the intellectuals and the politicians. Over the years, Chiadohas undergone several phases, as follows: in the past, this zone  was a center of diffusion of luxury; however, the decline occurred after 25 April 1974’s Revolution and the great fire that took place in 1988. Recently, the urban revitalization gave birth to an athmosphere of renaissance. Despite the opening of several Shopping Centers and the shifting of the main luxury brands to Avenida da Liberdade, Chiado still preserves an unparalleled importance both for followers of fashion and luxury lovers.
Keywords: Chiado; diffusion of fashion; urbanization in lisbon